2002
DOI: 10.1016/s0370-2693(02)02635-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactive quadratic gravity

Abstract: A quadratic semiclassical theory, regarding the interaction of gravity with a massive scalar quantum field, is considered in view of the renormalizable energymomentum tensor in a multi-dimensional curved spacetime. According to it, a self-consistent coupling between the square curvature term R 2 and the quantum field Φ(t, x) should be introduced in order to yield the "correct" renormalizable energy-momentum tensor in quadratic gravity theories. The subsequent interaction discards any higher-order derivative te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…To simplify this Lagrangian, we define the variable φ as f ′ (R) = φ, in terms of which the Lagrangian (7) reads…”
Section: The Phase Space Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify this Lagrangian, we define the variable φ as f ′ (R) = φ, in terms of which the Lagrangian (7) reads…”
Section: The Phase Space Of the Modelmentioning
confidence: 99%
“…In this context, renormalization of the energy-momentum tensor for a quantum field in a four-dimensional, curved space-time indicates that the presence of quadratic terms in the gravitational action is a priori expected [6]. On the other hand, Kleidis et al [7], demonstrated that, in quadratic gravity theories, an additional coupling arises between R 2 and any massive quantum scalar field, introducing a geometric source term in the wave equation for the quantum field.…”
Section: Introductionmentioning
confidence: 99%
“…with a purely geometric source. Although the equation L = 0 is not exactly a Klein-Gordon equation of the form (∂ 2 + m 2 + R/5)φ = αR 2 studied in [19], both theories appear to have a similar physical origin. It was shown that an effective re-normalized Lagrangian of the form αφR 2 is a result of dimensional consideration.…”
Section: Stability Of An Inflationary External Spacementioning
confidence: 97%
“…It was shown that an effective re-normalized Lagrangian of the form αφR 2 is a result of dimensional consideration. Indeed, the coupling constant α can only be made dimensionless, rendering a system free from introducing any additional arbitrary length scale, if the space-time dimension N = 6 [19]. Note that the scalar fields ψ and φ, both with dimension one, considered in this paper are designed to replace all dimensionful coupling constants with appropriate scalar fields.…”
Section: Stability Of An Inflationary External Spacementioning
confidence: 99%
See 1 more Smart Citation